Cirque du Freak - Shan, Darren (Boston Little, Brown and Company, 2001)
Two boys who are best friends visit an illegal freak show, where an encounter with a vampire and a deadly spider forces them to make life-changing choices.
Sequel: The vampire's assistant.
Keywords: Crepsley, Larten (Fictitious character) -- Fiction; Vampires -- Fiction; Spiders -- Fiction; Best friends -- Fiction; Friendship -- Fiction; Freak shows -- Fiction; Conduct of life -- Fiction; Horror stories